Peran Tax Avoidance sebagai Moderasi: Profitabilitas, Intensitas Modal, Ukuran Perusahaan, Solvabilitas - Andhito Rahmadhan Wijaya; Edy Subiyantoro; Prihat Assih (Magister Akuntansi Universitas Pancasila, 2023)
This study investigates the moderating role of Tax Avoidance in relation to profitability, solvency, capital intensity, and firm size. Data was processed using the statistical software SPSS. The results of the analysis indicate that the correlation between Return on Assets (ROA) and Debt Asset Ratio (DAR) exhibits a significant negative association. Firm size demonstrates a significant positive correlation with DAR, while capital intensity also shows a significant positive relationship with DAR. However, the interaction between ROA and Tax Avoidance does not exhibit statistical significance in its relationship with DAR. These findings illustrate that Tax Avoidance does not act as a moderator in the relationship between ROA and DAR. The outcomes of this study offer insights into how these elements can shape a company's financial structure and underscore the importance of considering the interactions among these variables in financial decision-making.